SENSORY PROFILE OF CHILLED CHEESECAKE MADE FROM DALI NI HORBO CHEESE IN CONSUMER PERCEPTION - Tristy Firlyanie Luthfi; P Jessica J. Josary; Selvi Novianti; Sandra Sanggramasari; Made Citra Yuniastuti (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
This research is a contribution to the use of dali ni horbo in the making of cheesecake and all the variations, so that consumer-based sensory profile characterization can be carried out. The purpose of this study was to determine the characteristics of the sensory profile and accelerate the cheesecake product development process. The method used in this study is an experiment that uses a consumer-based sensory profile characterization method. Later, it was known that the ideal dali cheesecake product according to panelists is cheesecake which has creamy color, dense texture, cheesy aroma and umami flavor. Dali cheesecake variant which was added with durian is a product that is considered close to the ideal product. Meanwhile, the sensory attributes of umami, dense and sweet are sensory attributes that were close to consumer preferences, but it was possible to do dali cheesecake development with other flavor variants.